Perceptions of parental provision of structure, autonomy support and psychological control and its effects on youth needs satisfaction, scholastic and athletic competence - Lim, Janna Ju Hong (2016)
In Self-Determination Theory, it is assumed that parenting dimensions have an important role in satisfying the basic psychological needs of autonomy, competence and relatedness in children. Research done have examined the importance of structure on developing competence, and when practiced either with autonomy support or psychological control, will result in differing youth outcomes. However there is a lack of research examining the relationship between the individual and combined effects of parental provision of structure, autonomy support and psychological control on psychological needs satisfaction, scholastic and athletic competence in youths. This study seeks to examine the moderating effects of psychological control on the relationship between parental provision of structure on psychological needs satisfaction, scholastic and athletic competence in youths, and how unique classes of youths with different combinations of these perceived parenting dimensions are associated with these same youth outcomes. Participants were university students (N = 214, 81 males, 133 females), aged 18 to 26 years (M = 22.60, SD = 1.81). Participants completed a self-reported online questionnaire. Linear Regression Analyses and Latent Profile Analyses (LPA) were conducted. The interaction between maternal provision of structure and psychological control negatively predicted scholastic competence. The three- class LPA solution revealed that autonomy support, relative to psychological control, is a more important predictor of psychological needs satisfaction, and parents could also be perceived to provide all three parenting dimensions at any one time. Thus, parents and educators should focus on providing autonomy support rather than psychological control, together with structure, when interacting with youths.